Contemporary techniques for remediating endocrine-disrupting compounds in various water sources: advances in treatment methods and their limitations - Katibi, Kamil Kayode; Yunos, Khairul Faezah; Che Man, Hasfalina; Aris, Ahmad Zaharin; Mohd Nor, Mohd Zuhair; Azis, Raba'ah Syahidah; Mohammed Umar, Abba (Multidisciplinary Digital Publishing Institute, 2021)
Over the years, the persistent occurrence of superfluous endocrine-disrupting compounds (EDCs) (sub µg L−1) in water has led to serious health disorders in human and aquatic lives, as well as undermined the water quality. At present, there are no generally accepted regulatory discharge limits for the EDCs to avert their possible negative impacts. Moreover, the conventional treatment processes have reportedly failed to remove the persistent EDC pollutants, and this has led researchers to develop alternative treatment methods. Comprehensive information on the recent advances in the existing novel treatment processes and their peculiar limitations is still lacking. In this regard, the various treatment methods for the removal of EDCs are critically studied and reported in this paper. Initially, the occurrences of the EDCs and their attributed effects on humans, aquatic life, and wildlife are systematically reviewed, as well as the applied treatments. The most noticeable advances in the treatment methods include adsorption, catalytic degradation, ozonation, membrane separation, and advanced oxidation processes (AOP), as well as hybrid processes. The recent advances in the treatment technologies available for the elimination of EDCs from various water resources alongside with their associated drawbacks are discussed critically. Besides, the application of hybrid adsorption–membrane treatment using several novel nano-precursors is carefully reviewed. The operating factors influencing the EDCs’ remediations via adsorption is also briefly examined. Interestingly, research findings have indicated that some of the contemporary techniques could achieve more than 99% EDCs removal.